The social lives of network effects: Speculation and risk in Jakarta's platform economy. (March 2023) - Nowak, Samuel
Under the designation "platform urbanism, " there is growing scholarly recognition that platform intermediaries are reconfiguring urban industries, processes, and relationships through the collection and manipulation of big data. Central to realizing this economic project is financial speculation on platforms' ability to coordinate network effects—a phenomenon in which the more users there are in a networked system, the more valuable and useful it becomes. In this paper, I argue that while the existing literature recognizes the importance of network effects, it has also adopted a limited conceptualization that understands platform firms as the primary agents generating and capturing the economic benefits of network effects. Drawing on 12 months of ethnographic fieldwork in Greater Jakarta, Indonesia, I work to expand this understanding through attention to the social lives of network effects—the ways in which platform architectures are always embedded in social relations created and sustained in everyday urban life. I show how ride-hailing drivers have attempted to mitigate the risks of their work through building socio-technical networks of their own, for their own purposes. Doing so reveals that it is not only platform firms and venture capital that speculate on network effects; rather, a range of actors in the city-region seek to tap into driver networks to advance their own social, political, and economic ends. In conclusion, I suggest that attending to these practices opens up space to reframe platform urbanism beyond its current preoccupation with macro political economic analyses, while also establishing new lines of inquiry for "speculative urbanism."